(untitled) (Journal Of Educational and Psychological Researches, 2015)
The present study aims at knowing the effect of instrumental enrichment in the acquisition of geographical concepts for first grade student in intermediate school. The study is restricted in the students of first grade student in intermediate school The EducationalDirectorate of Rusafa for academic (2013/2014),for the purpose of achieving the objective, the following hypotheses: There is no statistical significant different at the level of (0.5) between the scores of the experimental group who study geography according to the instrumental enrichment and the scores of the control group who learned geographical according to the traditional methods. In order to achieve theaims of the study with matched procedure which include two groups of the study. The sample attained (80) students in Al-Simoud intermediate school for girls in the experimental group and (40) students in the experimental group who are taught according to the method and (40) student in the control group who were taught in the control group. The researcher matched the two groups in terms of: (age in time, intelligence, previous year scores in Iraq Geography and previous knowledge in geography, parent’s acquisition). The researcher determined the material in the first semester for the academic year 2013/2014 in geography. It included the first four chapters in the boo The General Principles of Geography for the first grade – intermediate school. The experiment lasted 8 weeks. The researcher taught the two groups and at the end of the experiment. She applied the instrument of the study on the sample which is the acquisition posttest which she prepared in its final form in 50 items the type of multiple choice with four options. The distinction coefficient and the alternative difficulty were calculated by the use of t-test for two independent samples. The researcher used the statistical means like Pearson Coefficient and Chi-square. The results were as follows: The excel of the experimental group students who studiedgeography according to the instrumental enrichmentover the control group who learned geographical according to the traditional methods in acquisition pretest